PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PT. ASTRA HONDA MOTOR NAROGONG BEKASI. - Irawan Noor (Jurnal Ekonomi dan Industri, 2019)
The increasing demand for two-wheeled motorized vehicles, is an opportunity that continues to be considered to win the existing market competition. Customer loyalty is the key to winning an automotive competition. This study aims to analyze the effect of service quality and customer satisfaction simultaneously or partially on customer loyalty of PT. Astra Honda Motor Narogong Bekasi. This study involved 84 respondents. The results showed that service quality and customer satisfaction both simultaneously and partially on customer loyalty.